Securing the GCC in cyberspace - Clarke, Richard A.; Knake, Robert K. (Emirates lecture series, 2010)
This paper considers what such a safe cyber zone might comprise. It begins by assessing the risks posed to the GCC in cyberspace, including an assessment of threats from regional actors' cyber warfare capabilities and the vulnerabilities these actors could exploit, and a discussion of the potential consequences if these actors were to successfully target vulnerabilities with the GCC. It then lays out a roadmap for turning the GCC into a safe cyber zone